Design and Implementation of Automatic Switching for Water Level Control of Community Water Supply - Agus Ulinuha; M. Rusdi Wibowo (Urecol Journal. Part E: Engineering, 2022)
This paper presents design and implementation of Automatic Switching for controlling the water level in the reservoir of community water supply. The water supply system is energized by 2 sources i.e. power from utility grid and power generated by photovoltaic panels equipped with energy storage. The switching is based on the reservoir water level and determines the operation of submersible pump. The switching system employs electrode sensors in the water control level where 3 conditions are considered to control motor that drives the pump. The Automatic Switching is connected to Automatic Transfer Switch (ATS) that selects power sources to energize the pump, where it may be from the solar PV supported by storage system or from the grid. The selection is based on the remaining energy saved in the storage, when it is sufficient then it is used to energize the pump. Otherwise, the power from the grid is used to supply the pump. The combination of Automatic Switching and ATS determines when the pump is on and which power is taken to supply the pump. The manual system is complemented in the switching system to enable manual operation when the automatic system fails to work for some reason. The whole system is developed in a panel for easy operation and monitoring. The water level indicator is given in the panel for the purpose of adjusting the pump operation based on water level in the reservoir.